Bibliometric analysis for highly cited papers in operations research and management science from 2008 to 2017 based on Essential Science Indicators. (October 2019) - Liao, Huchang; Tang, Ming; Li, Zongmin; Lev, Benjamin
Highlights: A bibliometric analysis on ESI highly cited papers from 2008–2017 in OR/MS is given. We identify the most influential actors including journals, counties, and institutes. The co-authorship relations among countries, institutes and authors are given. The most cited papers are presented. Author keywords, keywords plus and words in title are analyzed. Abstract: The Essential Science Indicators (ESI) database is widely used to assess scientific outputs. The ESI database contains papers that entered the top 1% of sum citations in one discipline in the past ten years. Therefore, highly cited papers included in ESI database are of high quality in each field. This paper provides a bibliometric overview on the papers included in the ESI database in the field of operations research & management science. During the years of 2008–2017, there are 646 ESI highly cited papers in this area. Based on these 646 papers, we identify the most influential actors including journals, counties/regions, and institutes. The co-authorship relations among countries, institutes and authors characterize the collaboration status in the field of operations research and management science. The most cited papers are then presented. Finally, author keywords, keywords plus and words in title are analyzed, with hot research topics and future directions being provided.